TURKIC WORDS ADOPTED INTO PERSIAN UNTIL THE 19TH CENTURY (BASED ON PERSIAN EXPLANATORY DICTIONARIES) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines Persian explanatory dictionaries compiled in India from the time of Zahiriddin Muhammad Babur and the Mughal dynasty up to the 19th century, focusing on the presence of Turkic words within them. It also discusses the reasons for the inclusion of Turkic lexical items in these dictionaries and notes that such words are most frequently found in the fields of military-political affairs, everyday life, ethnography, and nature.